Cementless Versus Cemented Fixation in Total Knee Arthroplasty: Analysis of Regional Tibial Bone Density and Clinical Outcome - Wong, Daniel Wai-yip; Lee, Qunn-jid; Lo, Chi-kin; Law, Kenneth Wing-kin; Chang, Esther Wai-yee; Wong, Yiu-Chung (Clinics in orthopedic surgery, 2025)
Background: Cementless fixation in total knee arthroplasty (TKA) has theoretical advantages of being biological and bone preserving, but some surgeons are less confident in using it given previous reports of high failure rates in some implant designs. This study aimed to investigate the effect of fixation method on tibial bone density, clinical outcome, and survivorship. The main research question was whether fixation method would affect the postoperative change in tibial bone density in TKA. Methods: This study analyzed 53 cementless TKAs and 53 cemented TKAs of the same brand (Triathlon, Stryker). Digital radiological densitometry (DRD) was used to quantify the changes in regional tibial bone density (RTBD) within the first 2 years. Clinical outcome scores and survivorship were recorded. Results: Significant decreases in RTBD were observed in both groups in all tibial regions (p < 0.001 at all time points). RTBD was significantly higher in 7 of 8 tibial regions in cementless TKA at 6 months. The significance persisted in 2 regions of the lateral tibial condyle until the second year (p = 0.014 and p = 0.029). Clinical outcome scores (Knee Society Score, Western Ontario and McMaster Universities Osteoarthritis Index, and Forgotten Joint Score) were similar. No case of aseptic loosening was reported. Conclusions: Proximal tibial bone resorption was common in both cementless and cemented TKAs. Cementless fixation preserved more tibial metaphyseal bone globally at 6 months and at the lateral tibial condyle at 24 months. Its early clinical outcomes and survivorship were comparable to those of cemented fixation. KCI Citation Count: 0